2011
DOI: 10.3390/molecules161210123
|View full text |Cite
|
Sign up to set email alerts
|

The Dose-Effect of Icariin on the Proliferation and Osteogenic Differentiation of Human Bone Mesenchymal Stem Cells

Abstract: Icariin had been reported as a potential agent for osteogenesis, but the dose-effect relationship needed further research to realize the clinical application of icariin. We isolated and purified human bone mesenchymal stem cells (hBMSCs) and stimulated them with different concentrations of icariin. The cytotoxicity of icariin was evaluated by the methylthiazolytetrazolium (MTT) assay method. The proliferation and osteogenic differentiation of such hBMSCs were investigated for different concentrations of icarii… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(86 citation statements)
references
References 15 publications
4
79
1
2
Order By: Relevance
“…These results are consistent with the proliferation and mineralization stages in the growth of the osteoblast-like MC3T3-E1 cells [29]. Our data showed that the tested flavonoids did promote osteoblast proliferation and differentiation, consistent with reports in recent literature [21,30,31]. In addition, we found that epimedin B and epimedin C were more potent than icariin.…”
Section: Effects Of Identified Compounds On Alp and Ca Content Expressupporting
confidence: 95%
“…These results are consistent with the proliferation and mineralization stages in the growth of the osteoblast-like MC3T3-E1 cells [29]. Our data showed that the tested flavonoids did promote osteoblast proliferation and differentiation, consistent with reports in recent literature [21,30,31]. In addition, we found that epimedin B and epimedin C were more potent than icariin.…”
Section: Effects Of Identified Compounds On Alp and Ca Content Expressupporting
confidence: 95%
“…Independent studies have previously confirmed that icariin is a potent inducer for osteogenic differentiation of MSCs [1,11,12]. As a promising drug to facilitate MSC-based bone regeneration, the mechanism of icariin-induced osteogenic differentiation attracted significant attention.…”
Section: Discussionmentioning
confidence: 99%
“…It could be concluded from these findings that icariin treatment activated PI3K/Akt and osteoblasts by independent research groups [10,11]. The drug was determined clinically safe and approved for use in drug preparations [1,11,12]. The application of icariin to enhance osteogenic differentiation of MSCs was promising.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Until a certain dosage is used, no optimum effect can be determined. Dose-effect relation is referring to the increase or decrease of herbal dosage (concentration) which will ultimately correspond to a stronger or weakened therapeutic effect [1].…”
Section: Introductionmentioning
confidence: 99%